Sistem Pendukung Keputusan Kenaikan Jabatan Pada Bank BTPN Menggunakan Metode Analytic Hierarchy Process - Nurdin Nurdin; Yeni Yeni (Teknik Informatika Universitas Malikussaleh, 2015)
In accordance with the rules set Bank BTPN the branch of lhokseumawe conducting the process of the increase in office, then the necessary criteria to determine who will be selected to fill the position that has been determined. In the process of determining the position required a decision support system. One method that can be used for decision support Systems is to use the method of Analytic Hierarchy Process. This method was chosen because it was able to calculate the best value from a number of existing employees, in this case the candidate meant that employees who are entitled to occupy positions that are available based on the criteria specified. Research done by searching for the value weights for each criterion and an alternative calculation process then conducted a global alternative that will determine the best employees.